Progress in low-frequency microwave absorbing materials - Jia, Zirui; Lan, Di; Lin, Kejun; Qin, Ming; Kou, Kaichang; Wu, Guanglei; Wu, Hongjing (Journal of materials science. Materials in electronics, 2018)
Electromagnetic wave equipment and devices working at low frequency of 0.5–8 GHz have been extensively used in wireless data communication systems, local area network, household appliances and so on. It is found that the extensive use of such devices have a terrible pollution to their surroundings and moreover threaten the health of human being by weakening biological immune systems, breaking DNA strands, promoting cancers. A key solution to this problem is to develop materials that are able to attenuate the harmful electromagnetic waves pollution. This review aims at summarizing the progresses obtained in conventional materials and new emerging structures for microwave absorption at low frequency. The ultimate aim of these materials is to realize a wider effective absorption frequency bandwidth ( f E ) at a thinner coating thickness ( d ). Typical and well-received component and construction of composite, synthesis methods, and f E are summarized in several tables in detail. The different characteristics of different types of absorbing materials are given much attention in this review.